2021
DOI: 10.2147/jpr.s282736
|View full text |Cite
|
Sign up to set email alerts
|

Promising Effect of Visually-Assisted Motor Imagery Against Arthrogenic Muscle Inhibition – A Human Experimental Pain Study

Abstract: Purpose Clinically, arthrogenic muscle inhibition (AMI) has a negative impact on functional recovery in musculoskeletal disorders. One possible technique to relieve AMI is motor imagery, which is widely used in neurological rehabilitation to enhance motor neuron excitability. The purpose of this study was to verify the efficacy of visually-assisted motor imagery against AMI using a human experimental pain model. Methods Ten healthy volunteers were included. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(78 reference statements)
1
9
0
Order By: Relevance
“…As stated, these similarities can be interpreted as compensatory changes in response to arthralgia and limb deformations. Furthermore, the weakness and atrophy of the calf muscles could be attributed even to the arthrogenic muscle inhibition (AMI), a presynaptic reflex inhibition of the periarticular musculature elicited by abnormal input to the joint, such as swelling and pain [ 17 ], although no pain or ankle impairment that could account for this condition was present in the two children.…”
Section: Discussionmentioning
confidence: 99%
“…As stated, these similarities can be interpreted as compensatory changes in response to arthralgia and limb deformations. Furthermore, the weakness and atrophy of the calf muscles could be attributed even to the arthrogenic muscle inhibition (AMI), a presynaptic reflex inhibition of the periarticular musculature elicited by abnormal input to the joint, such as swelling and pain [ 17 ], although no pain or ankle impairment that could account for this condition was present in the two children.…”
Section: Discussionmentioning
confidence: 99%
“…Motor Imagery. Motor imagery, mental practice/simulation of motor actions, has been shown to increase excitability 170 and activation 171 of neurons within the motor cortex and spinal cord [172][173][174] in healthy individuals. Motor imagery techniques have been successfully applied poststroke in conjunction with traditional therapies to improve upper-extremity function, 175,176 but significant heterogeneity in the parameters/approach and population characteristics may contribute to inconsistent results.…”
Section: Emerging Interventionsmentioning
confidence: 99%
“…177 Although not studied as much in orthopedic rehabilitation, researchers using an ankle effusion model demonstrated the ability of motor imagery to directly enhance motor neuron pool excitability. 172 Furthermore, a randomized controlled trial found that 4 weeks of motor imagery practice in conjunction with standard of care rehabilitation preserved quadriceps strength following total knee arthroplasty. 178 Considerations for the near-limitless variability in parameters (eg, supervision, guided/unguided, location, body position, perspective, focus, length of practice, and more) of motor imagery must be made when incorporating this intervention in treatment.…”
Section: Emerging Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Known without any adverse effect, this practice may be combined with sensory modalities or used in conjunction with other disinhibitory interventions targeting different neural pathways to achieve the ideal therapeutic goal for AMI treatment. 15,28 Interestingly, the effect of a novel neuromotor reprogramming (NR) treatment based on the use of proprioceptive sensations associated with motor imagery and low frequency sounds (LFS) has not been studied in AMI after knee injuries. Fundamentally, motor imagery and movement execution share substantial overlap of active brain regions that may minimize AMI and quadriceps dysfunction.…”
mentioning
confidence: 99%